Combining ability of different yield related characters in Rice (SAARC Journal of Agriculture, 2015)
Combining ability for yield and yield contributing character of rice was studied using five lines IR79156A, BRRI7A, BRRI33A, BRRI21A and IR75608A and four testers BRRI20R, BRRI31R, BRRI26R and BAU521R to produce 20 F1 in line × tester fashion. The variances due to SCA were larger than the variance due to GCA for all the characters which indicate the prevalence of non-additive gene action. BRRI7A/BRRI31R cross combination was the best specific combiner for grain yield/plant. The predominance of non-additive genetic components was observed for all the traits which indicated that the improvement of the characters with greater non-additive genetic component could be contemplated for the exploitation of heterosis. Estimates of GCA effects showed that maternal line BRRI33A and paternal tester BRRI31R was an excellent general combiner for improving yield contributing traits. The cross IR79156A/BRRI20R was found as good specific combiner for most of the yield contributing traits viz., panicle length, panicle weight, number of spikelet/panicle, spikelet fertility, 1000 grain weight, harvest index and grain yield/plant. The cross between good general combiners did not always produce the best specific crosses. Moreover, the predominance of the production of the best specific crosses from high × low and low × low combiners indicated the influence of non-additive and over dominant gene actions on the yield and yield contributing traits. DOI: http://dx.doi.org/10.3329/sja.v12i2.21926 SAARC J. Agri., 12(2): 143-153 (2014)